Competitiveness of Sweet Orange Value Chain in Sindhuli District, Nepal - K.C, Prabhat; Dhakal, Shiva Chandra; Kattel , Rishiram; Adhikari, Rajkumar; K.C. , Prabha; Regmi , Bandana (Journal of the Institute of Agriculture and Animal Science, 2024)
Government of Nepal declared sweet orange super zone in Sindhuli for increasing the productivity and better commercialization of product. This study analyzed sweet orange value chain in Sindhuli with the aim of identification of major value chain actors along with value chain competitiveness, structure, conduct and performance. A Survey was done with 150 producers, 5 retailers and 4 agro vets, 8 banks and co-operatives, 2 processing industry and 2 nurseries using random sampling method in 2021. The findings revealed the involvement of two channels in value chain stream of sweet orange. A total of 17% was transacted through first channel via collectors and second channel transacted 83% of fruits via local traders. Sweet orange market was found oligopolistic along the chain. The business was found profitable with B/C ratio 1.37 in study area. Relatively better institutional set up on extension services, better technological adoption rate was driving factors for profitability. Value chain stream of Sindhuli had better market margin, market efficiency and value addition. Policy efforts to strengthen local institutions, insurances, market information and credits are recommended to improve performance of value chain. Processing and value addition of sweet orange should be of concern to government for enhancing export potentiality.